The Utilization of Coconut Wastes for Bioplastic Production - Villalobos, J. Rodolfo Rendón (International Journal For Research In Agricultural And Food Science, 2020)
Plastics have been developed as materials with specific characteristics to market demands (durable, economical and light). However, single-use plastic waste is a worldwide event due to its low or no biodegradability. Pollution problems related to the disposal of solid waste associated with these polymers, both in the agricultural sector, companies and society in general, have generated the search for alternatives that help reduce the impact generated by these materials. The objective of this work was to take advantage of the coconut bagasse (Cocos nucifera L.) in obtaining natural polymers that allow the production of bioplastics. The microcellulose was characterized by scanning electron microscopy (SEM) and its thermal capacity and percentage of crystallinity were determined by Differential Scanning Calorimetry (DSC). The microcellulose was dispersed in starch/glycerol to obtain bioplastics as follows: control C or starch/glycerol with no microcellulose addition; A1 or starch/glycerol and microcellulose at 0.05% and A2 or starch/glycerol and microcellulose at 0.1%, respectively. The SEM of cellulose showed the removal of lignocellulosic walls, as well as fibers with diameters 40 and 400 μm. The native fiber presented an endotherm at 116.41°C and the microcellulose at 143.67°C. The bioplastics observed by SEM presented a surface with irregularities, it was grainy, not soft, and at first glance you could see some large particles associated with processing operations. Sample A1 presented the best calorimetric characteristics. Obtaining bioplastics materials from coconut residues will help mitigate the production and excessive use of single-use materials.